Chamber Music of the Second Half of the 20th Century as a Form of International Cultural Dialogue and Self-Identification - Pylatyuk, Ihor; Sydorenko, Lyubava; Katrych, Olha; Chubak, Antonina (Journal of History Culture and Art Research, 2020)
The article deals with the study of the main tendencies of European chamber music of the second half of the 20th century as a special creative "oasis", which in the conditions of globalization processes ensures the realization of inter-ethnic cultural dialogue and awareness of ethnic identity. The most extensive body of artistic achievements in the field of chamber vocal-instrumental genres is found in representatives of the Katowice (Poland) and Lviv (Ukraine) composer schools. The genres of chamber cantata and chamber vocal and instrumental cycle most clearly and consistently represent the achievements of both of these national musical traditions. A common model of imitation for them is the Western European chamber-vocal music of the 19th century, and the unifying factor is the preservation of national specificity of thinking. In the second half of the 20th century, Polish musical culture is becoming an integral artistic phenomenon on a European scale. In the Ukrainian musical culture of this period, the tendencies for experimentation are gradual, with an emphasis on national traditions and folklore sources. The last third of the 20th - the beginning of the 21st centuries, the Ukrainian and Polish music (in particular, in the Lviv and Katowice Composer Schools) marked by the synchronicity of the ways of development, the intensification of innovative searches against the background of the postmodern cultural situation, where the concept of "tradition" takes on the importance of individual and authorial rethinking; and the process of dramatic updating of the genre of chamber vocal and instrumental music genres begins.